Programové rozpočtovanie ako jedno z prínosov reformy verejných financií - Baláži, Peter (Univerzita Pardubice, 2010)
The aim of this text is to advert on implementation’s necessity of performance budgeting in the level of local self-government, to analyse advantages, which it brings along and on the example of the particular village to explain method of compilation of the performance budget and his form. The result of the thesis’s exploration is that implementation of performance budgeting is the sign of modern approach to the using of public resources. We made a conclusion, that the performance budget has higher information’s value and it forms the base for the budgeting of the medium-term expenses.
Keywords: reform of state government; local self-government; performance budgeting; expenses of the local budget; efficiency; transparency